A size-dependent thermodynamic model for coke crystallites: The carbon–hydrogen system up to 2500 K. (April 2015) - Ouzilleau, Philippe; Gheribi, Aïmen E.; Eriksson, Gunnar; Lindberg, Daniel K.; Chartrand, Patrice
Abstract: The development is presented of a model of the thermodynamic functions of enthalpy, entropy and Gibbs energy for the elements carbon and hydrogen in coke crystallites. It is applicable to varying degrees of graphitization, described by the crystallite length La and the crystallite height Lc . The model parameters are derived from known properties such as bond enthalpies and entropies of formation. Good agreement has been obtained between the predicted thermal dehydrogenation of petroleum cokes and experimental data. The removal of hydrogen from idealized coke crystallites is predicted to occur mostly between 1100 and 1300 K. Agreement has also been found in the comparison of the predicted thermodynamic stability of coke relative to graphite, in a previous experimental study. This stability has been determined as at ≈900 J g −1 at temperatures between 950 and 1250 K and for La = 10 nm. The current predictive capacity of the present model is valid for temperatures up to 2500 K.